Photosensitivity of barium germano-gallate glasses under femtosecond laser direct writing for Mid-IR applications. Issue 24 (15th December 2021) - Yao, Heng; Zaiter, Rayan; Cavillon, Maxime; Sapaly, Benjamin; Calzavara, Florian; Delullier, Pierre; Cardinal, Thierry; Dai, Ye; Poumellec, Bertrand; Lancry, Matthieu
Abstract: Barium germano-gallate glasses are attractive glass hosts for photonic applications in the mid-infrared region up to 6 μm. In this work, we investigate the photosensitivity of such glasses under femtosecond laser, with an emphasize on the formation of refractive index changes. Six glasses with varying compositions (including addition of K, Na, Y, and La) were studied. We observed several transformation regimes in the pulse energy – repetition rate landscape: Type I (isotropic refractive index change) and a spatial broadening regime with a phase shift Δϕ > 2π rad at 550 nm. This translates into refractive index changes Δn > 10 −2 and is comparable to values obtained in most chalcogenide glasses. The effect of glass composition on Δϕ appears correlated to the number of non-bridging oxygen presented in the glass and is brought to evidence by monitoring the Cations/GaO3/2 ratio. This provides a way to design a range of germano-gallate glasses suitable to imprinting high refractive index contrast.